100 THERAPY-RELATED ACUTE NONLYMPHOBLASTIC LEUKEMIA AFTER MITOXANTRONE THERAPY IN A PATIENT WITH MULTIPLE SCLEROSIS. (1st January 2006) - Sumrall, A. L.; Dreiling, B.
Abstract : Mitoxantrone is the first FDA-approved agent for the treatment of secondary progressive multiple sclerosis. It is a synthetic anthracenedione that impairs DNA repair and affects T cells, B cells, and macrophages. The incidence of leukemia associated with mitoxantrone is estimated at 0.07%. A 58-year-old male with a past medical history of migraine headaches, complex partial epilepsy, and secondary progressive multiple sclerosis (diagnosed in 1975) was admitted to our facility in August 2005 with febrile neutropenia, pneumonia, and declining mental status. Admission hemogram revealed profound leukopenia (leukocytes 700/cmm with absolute neutrophil count of 308), macrocytic anemia (hematocrit 35.1%), and marked thrombocytopenia (platelets 54, 000/cmm). He received treatment with 148 mg of mitoxantrone from May 2003 to April 2005. He also received weekly interferon-beta-1a. Admission peripheral smear showed normal neutrophils and lymphocytes and no immature myeloid or erythroid precursors. Marrow was replaced by poorly differentiated myeloid cells with predominance of myeloblasts and promyelocytes; few normal erythroid and megakaryocytic precursors were seen. By flow cytometry, the cells were positive for CD13, CD33, CD117, CD2, CD68, and CD38 but negative for CD34, CD10, and HLA-DR. As his respiratory and renal functions deteriorated, he required mechanical ventilation and hemodialysis. He was treated with the 3 + 7 regimen of daunorubicin and cytosine arabinoside. Two weeks later, repeat marrow showed normal recovery, as did peripheral counts. In spite of aggressive support with blood products, antibiotics, and antifungals, his mental status worsened. Contributing to his demise were recurrent intracranial hematomas and subarachnoid hemorrhage. This patient developed acute leukemia 27 months after initiation of mitoxantrone. He satisfied criteria for therapy-related acute leukemia as he denied prior chemotherapy or radiation exposure and had no familial or personal risk factors for leukemia. Review of the literature reveals 10 reported cases of nonlymphoblastic leukemias following treatment with mitoxantrone. This case continues the important discussion of efficacy versus toxicity when selecting mitoxantrone as a therapeutic option for patients with multiple sclerosis. Although leukemia is rarely seen, the potential for this outcome warrants careful consideration prior to initiation of therapy.